A preliminary report on the role of lay counselling amongst patients with inflammatory bowel disease. - Godber, D (1988)
A team of lay counsellors was trained by the Nottingham Counselling Centre to provide advice to members of the East Midlands branch of the National Association for Colitis and Crohn's Disease. Initial contact was by telephone and the results of the first 25 client/counsellor discussions are presented. Twenty enquiries were made directly by the patient and 5 by a relative of the patient. All but two of the patients were women. The median age of the patients was 52 years with a median duration of symptoms of 3 years. A failure of communication between the patient and other people underlay most of the problems discussed. Eighteen people welcomed the opportunity simply to talk; in 10 cases there was little rapport with their own doctor and in 8 cases people felt too embarrassed to discuss their problems with friends or relatives. This sense of isolation had been anticipated by counsellors from their own experience and may be a substantial, but as yet unrecognized problem amongst many patients with inflammatory bowel disease.